2019
DOI: 10.3389/fpsyg.2019.00051
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Response Time and Responses in Multidimensional Health Measurement

Abstract: This study explored calibrating a large item bank for use in multidimensional health measurement with computerized adaptive testing, using both item responses and response time (RT) information. The Activity Measure for Post-Acute Care is a patient-reported outcomes measure comprised of three correlated scales (Applied Cognition, Daily Activities, and Mobility). All items from each scale are Likert type, so that a respondent chooses a response from an ordered set of four response options. The most appropriate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…We use the word answering time as a broad concept, including response time (RT), which is the amount of time in which a student responds to the question item after it is shown on the screen; RT stamp (the time of day when a student accesses the survey form); and answer date (the number of days elapsed in which a student completes the survey after it was announced). In particular, RT has recently attracted attention mainly in psychological assessment and educational testing; however, little is known about how to use RT in mental health measurement [ 25 , 26 ]. A few studies have shown that RT is related to depression estimation and the prediction of suicide ideation and attempt status [ 25 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…We use the word answering time as a broad concept, including response time (RT), which is the amount of time in which a student responds to the question item after it is shown on the screen; RT stamp (the time of day when a student accesses the survey form); and answer date (the number of days elapsed in which a student completes the survey after it was announced). In particular, RT has recently attracted attention mainly in psychological assessment and educational testing; however, little is known about how to use RT in mental health measurement [ 25 , 26 ]. A few studies have shown that RT is related to depression estimation and the prediction of suicide ideation and attempt status [ 25 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…CAT based on multidimensional IRT models has also been proposed to efficiently measure multiple traits at the same time (e.g., Seo & Weiss, 2015; Wang et al, 2019; Yao et al, 2014; Zheng et al, 2013). Such CAT algorithms based on multidimensional IRT models are statistically and computationally intense.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research scenario of LPRM can be expanded, such as establishing a pattern recognition framework for the MCAT with polytomous items. Note that for the multidimensional graded-response data, the MGRM is an essential compensatory MIRT model for the paper-and-pencil test or the MCAT (e.g., Jiang et al, 2016;Depaoli et al, 2018;Tu et al, 2018;Wang et al, 2018a, Wang et al, 2019Nouri et al, 2021), so it is necessary to extend the item-trait pattern recognition idea for the items with dichotomous responses to those with graded responses. Moreover, the LPRM was developed directly based on the M2PLM.…”
Section: Introductionmentioning
confidence: 99%